Viral suppression and adherence among HIV-infected children and adolescents on antiretroviral therapy: results of a multicenter study - Maria L.S. Cruz; Claudete A.A. Cardoso; Mariana Q. Darmont; Edvaldo Souza; Solange D. Andrade; Marcia M. D'Al Fabbro; Rosana Fonseca; Jaime G. Bellido; Simone S. Monteiro; Francisco I. Bastos (Elsevier, 2014)
Objective: To evaluate treatment adherence among perinatally-infected pediatric human immunodeficiency virus (HIV) patients followed in pediatric centers in Brazil. Methods: This was a cross-sectional multicenter study. Medical records were reviewed and adherence scale, assessment of caregivers' quality of life (WHOQOL-BREF), anxiety, depression, and alcohol/substances use/abuse were assessed. Outcomes included self-reported 100% adherence in the last three days and HIV viral load (VL) < 50 copies/mL. Statistical analyses included contingency tables and respective statistics, and multivariable logistic regression. Results: 260 subjects were enrolled: 78% children and 22% adolescents; 93% of caregivers for the children and 77% of adolescents reported 100% adherence; 57% of children and 49% of adolescents had VL < 50 copies/mL. In the univariate analyses, HIV diagnosis for screening due to maternal infection, lower caregiver scores for anxiety, and higher scores in physical and psychological domains of WHOQOL-BREF were associated with 100% adherence. Shorter intervals between pharmacy visits were associated with VL < 50 copies/mL (p ≤ 0.01). Multivariable regression demonstrated that caregivers who did not abuse alcohol/other drugs (OR = 0.49; 95% CI: 0.27-0.89) and median interval between pharmacy visits < 33 days (OR = 0.97; 95% CI: 0.95-0.98) were independently associated with VL < 50 copies/mL; whereas lower caregiver scores for anxiety (OR = 2.57; 95% CI: 1.27-5.19) and children's HIV diagnosis for screening due to maternal infection (OR = 2.25; 95% CI: 1.12-4.50) were found to be independently associated with 100% adherence. Conclusions: Pediatric HIV programs should perform routine assessment of caregivers' quality of life, and anxiety and depression symptoms. In this setting, pharmacy records are essential to help identify less-than-optimal adherence. Resumo: Objetivo: Avaliar a adesão ao tratamento antirretroviral entre portadores de HIV acompanhados em centros pediátricos. Métodos: Trata-se de estudo transversal multicêntrico. Os prontuários ambulatoriais foram revistos e aplicadas escala de adesão, avaliação de qualidade de vida (WHOQOL-BREF), ansiedade, depressão e uso indevido de álcool/substâncias entre cuidadores. Os desfechos incluíram autorrelato 100% de adesão nos últimos três dias e carga viral do HIV (CV) < 50 cópias/mL. Resultados: 260 indivíduos foram incluídos, 79% crianças e 21% adolescentes; 93% das crianças e 77% dos adolescentes relataram 100% de adesão; 57% das crianças e 49% dos adolescentes tinham CV < 50 cópias/mL. Na análise univariada, diagnóstico do HIV por triagem devido à infecção materna, cuidador com pontuação menor para ansiedade e maior nos domínios físico e psicológico do WHOQOL-BREF se mostraram independentemente associados a 100% de adesão. Intervalos mais curtos entre visitas de farmácia foram associados com CV < 50 cópias/mL (p ≤ 0,01). Regressão multivariada mostrou que os cuidadores sem abuso de álcool/outras drogas (OR = 0,49; IC95% 0,27-0,89) e o intervalo médio entre visitas de farmácia < 33 dias (OR = 0,97; IC95% 0,95-0,98) foram associados com CV < 50 cópias/mL; cuidador com menores escores para ansiedade (OR = 2,57; IC95% 1,27-5,19) e diagnóstico de crianças por triagem devido à infecção materna (OR = 2,25; IC95% 1,12-4,50) foram associados com 100% de adesão. Conclusões: Programas de HIV pediátrico devem avaliar qualidade de vida e sintomas de ansiedade e depressão dos cuidadores. Registros de farmácia são essenciais na identificação de adesão insatisfatória. Keywords: Adherence, HIV-infected children, HIV-infected adolescents, Antiretroviral treatment, Palavras-chave: Adesão, Crianças vivendo com HIV, Adolescentes vivendo com HIV, Tratamento antirretroviral